The Effects Of High-Fat Diet On The Molecular Pathways In Cardiac Tissue: A Systematic Review Of In Vivo Rodent Studies And Integrated Bioinformatic Analysis - Muhammad Syaffuan Ahmad Najib; Marjanu Hikmah Elias; Norsham Juliana Nordin; Siti Hamimah Sheikh Abdul Kadir; Effendi Ibrahim; Nazefah Abdul Hamid (MDPI, 2026)
Indexed by WOS / SCOPUS / ERA